INTERNATIONAL AND EUROPEAN STANDARDS OF LONG-TERM CARE: TOWARDS THE EMERGENCE OF A DERIVED SOCIAL RIGHT - Dragićević Đorđević, Marija (COLLECTION OF PAPERS, FACULTY OF LAW NIŠ, 2026)
This paper analyses the normative role of international and European standards in shaping the right to long-term care. It proceeds from the premise that long-term care is not formulated as an autonomous social right in positive international law, yet its legal content may be derived from the broader corpus of human rights, in particular the right to social security. In this context, the paper examines relevant universal standards developed within the framework of the United Nations and the International Labour Organization, as well as the European normative framework established within the system of the Council of Europe and European Union law. Through normative analysis, it is demonstrated that the cumulative effect of these sources progressively gives rise to legally binding positive obligations of the state, as well as to a minimum normative core in the field of long-term care, encompassing the provision of available, accessible, high-quality and non-discriminatory support services for persons in a state of functional dependency. Long-term care can therefore no longer be regarded solely as a matter of social policy, but increasingly as a derived legal category aimed at ensuring a dignified life, social inclusion, and the independence of persons dependent on care and assistance.